PENGARUH PENGGUNAAN MEDIA PEMBELAJARAN DIGITAL SEBAGAI BAHAN AJAR TERHADAP PRESTASI BELAJAR SISWA SD DALAM MATA PELAJARAN IPS - Dilla Rahayu; Davinah Fauzah; Silvi Samrotul Fuadah; Dhea Syfa Ananda; Melisa Andriani; Vina Azzahra Syifa Fauziyah; Yuyun Dwi Haryanti (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2025)
This study aims to examine the effect of using digital learning media as instructional materials on elementary school students’ learning achievement in Social Studies. The research employed a literature study approach by analyzing 25 relevant research articles published within the last five years. The findings indicate that digital learning media have a significant positive effect on improving students’ Social Studies achievement. Various forms of digital media, including animated videos, interactive multimedia, digital flipbooks, Android-based applications, and digital quiz platforms, were found to enhance students’ learning motivation, conceptual understanding, and engagement in the learning process. Furthermore, the effectiveness of digital learning media is influenced by teachers’ digital competence, the quality of media design, and the availability of supporting facilities and infrastructure in schools. These findings highlight the importance of strengthening teachers’ digital literacy and developing digital learning media that align with the characteristics of elementary school students. Future research is recommended to investigate the effectiveness of specific types of digital media in greater depth, particularly in relation to different Social Studies skill domains.